Evaluation of Equisetin as an Anti-Microbial and Herbicidal Agent from Endophytic Fungus Fusarium sp. JDJR1 - Wei Wei; Ping Chen; Babar Khan; Kailin Tian; Yang Feng; Bei Lv; Nasir Ahmed Rajput; Wei Yan; Yonghao Ye; Guiyou Liu (Agronomy, 2023)
Equisetin was isolated from endophytic fungus Fusarium sp. JDJR1 via bioassay-guided isolation, and it was evaluated as an anti-microbial and herbicidal agent. Bioactivity assessments revealed that equisetin exhibited a broad spectrum of fungicidal and anti-bacterial activity against various plant pathogens. The EC50 values against Botrytis cinerea, Fusarium graminearum, Sclerotinia sclerotiorum, and Rhizoctonia solani ranged from 10.7 to 21.0 μg/mL. Notably, equisetin demonstrated activity against Xanthomonas oryzae pv. oryzicola, Xanthomonas oryzae pv. oryzae and Pseudomonas solanacearum with an MIC range of 4–16 μg/mL, surpassing the efficacy of the positive control: streptomycin sulfate. Equisetin, at a concentration of 100 μg/mL, could completely inhibit the spore germination of F. graminearum. In in vivo protection experiments, the protective efficacy of equisetin against B. cinerea on tomato fruits at 200 μg/mL reached 72.9%. Furthermore, in herbicidal activity tests that use the Petri dish bioassay method, equisetin had a good inhibitory effect on the root growth of weeds. At a concentration of 100 μg/mL, the inhibition rates for Echinochloa crusgalli and Eclipta prostrata root were 98.8 and 94.4%, respectively.